2017
DOI: 10.1016/j.jval.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole Lauroxil Compared with Paliperidone Palmitate in Patients with Schizophrenia: An Indirect Treatment Comparison

Abstract: These results suggest that both AL and PP are effective for treatment of adults experiencing acute exacerbation of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(51 reference statements)
2
3
0
Order By: Relevance
“…The second most relevant result of this work is that we did not identify significant differences in tolerability and effectiveness profiles between the Ari-LAI and the PP1M/PP3M groups. While, on the one hand, this could be explained by the reduced sample size, it should, however, be considered that this data remains in continuity with both what was assessed in our previous study [ 16 ] and similar researches [ 34 , 35 ]. Indeed, a retrospective study in a real-world clinical setting comparing the effectiveness of 1 year treatment with Ari-LAI, haloperidol LAI and PP1M in a sample of patients with SCZ identified similar tolerability and effectiveness profiles [ 36 ].…”
Section: Discussionsupporting
confidence: 84%
“…The second most relevant result of this work is that we did not identify significant differences in tolerability and effectiveness profiles between the Ari-LAI and the PP1M/PP3M groups. While, on the one hand, this could be explained by the reduced sample size, it should, however, be considered that this data remains in continuity with both what was assessed in our previous study [ 16 ] and similar researches [ 34 , 35 ]. Indeed, a retrospective study in a real-world clinical setting comparing the effectiveness of 1 year treatment with Ari-LAI, haloperidol LAI and PP1M in a sample of patients with SCZ identified similar tolerability and effectiveness profiles [ 36 ].…”
Section: Discussionsupporting
confidence: 84%
“…The extent of these reductions was similar, with the range of mean differences spanning from −8.12 to −12.01, with overlapping 95% credible intervals. These results, in addition to a similar incidence of TEAEs for both AL and PP, supported the finding that AL and PP were equally efficacious [ 98 ].…”
Section: Clinical Studies: Safety and Efficacysupporting
confidence: 83%
“…12,13 Although a newer study reported that psychotropic medication non-adherence was high, and was influenced by various factors (such as patients' individual behavior, social or family support, clinical or illness and treatment-related, and overall health care systemrelated factors) operating at different levels, 14 LAI formulations of paliperidone palmitate 3-monthly (PP3M), aripiprazole, olanzapine, and paliperidone palmitate once-monthly (PP1M) showed the highest effect sizes and certainty of evidence for both relapse prevention and acceptability in the maintenance treatment of adults with nonaffective psychoses. 15 Thus, LAI antipsychotics (LAIAs) may promote the development in the later stages of schizophrenia, and introducing the patient to a long-acting formulation for ongoing maintenance therapy while treating acute psychotic episodes, [16][17][18][19] or nonaffective psychoses 15 may assist clinicians in establishing optimal treatment strategies.…”
Section: Introductionmentioning
confidence: 99%